Small Entrepreneurship in Russia: Development Trends, Structural Changes, Rating Assessment of Regions - Bakanach, Olga V.; Dubrova, Tatiana A.; Esenin, Mikhail A.; Blinova, Svetlana V. (International Review of Management and Marketing, 2016)
The assessment of the small business condition in Russia is given in the paper, tendencies in its development taking into account various size groups of companies are revealed. The different character of development dynamics of micro, small and medium-sized enterprises that does not allow drawing a conclusion on the sustainable development of small and medium entrepreneurship sector increasing small business validity is shown. As well as comparison of key characteristics of small business development values in Russia and European Union (EU) countries is carried out. The paper shows that the potential of small business in Russia is not revealed to the full, its competitive advantages are not attained. The need when developing programs on stimulation and support for small business is shown that considers both its branch features and regional heterogeneity in development. The approach to rating assessment of regions according to the level of small business development is suggested, thus the attention is paid both to formation of the covered set of features and justification of the calculation procedure. The advantages of the suggested approach to rating formation are implementation simplicity, immunity to outliers (discordant observation), possibility for use of the correlated features, objectivity of the choice of weighting coefficients on the basis of the information value (importance) of the considered factors. The research findings allow receiving the flag information targeted at taking reasonable measures in accordance with small business support, differentiated according to regions. Keywords: Small business; Exploratory data analysis; Correlation analysis; Principle component method; Rating assessment. JEL Classifications: C38; L26; R58